2013
DOI: 10.1016/j.jmbbm.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial mechanobiology, skin wound healing, and the stem cell niche

Abstract: Skin wound healing is a vital process that is important for re-establishing the epithelial barrier following disease or injury. Aberrant or delayed skin wound healing increases the risk of infection, causes patient morbidity, and may lead to the formation of scar tissue. One of the most important events in wound healing is coverage of the wound with a new epithelial layer. This occurs when keratinocytes at the wound periphery divide and migrate to re-populate the wound bed. Many approaches are under investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
204
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 95 publications
2
204
0
7
Order By: Relevance
“…As wound healing is a critical process that re-establishes the epithelial barrier following disease or injury, poor wound healing increases infection risk, causes patient morbidity, and may lead to the scar formation. If there is a defect in the stem cell niche, wound repair could be delayed by the abnormal response of stem cells to injury [5] . Thus, understanding how to recreate the stem cell niche is key to regenerative medicine applications.…”
Section: The Stem Cell Niche In Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…As wound healing is a critical process that re-establishes the epithelial barrier following disease or injury, poor wound healing increases infection risk, causes patient morbidity, and may lead to the scar formation. If there is a defect in the stem cell niche, wound repair could be delayed by the abnormal response of stem cells to injury [5] . Thus, understanding how to recreate the stem cell niche is key to regenerative medicine applications.…”
Section: The Stem Cell Niche In Regenerative Medicinementioning
confidence: 99%
“…Thus, the interaction between stem cell-associated integrins and the ECM may be important in shaping the epidermal stem cell niche. In addition to the ECM and integrins, growth factors or mechanobiological factors can also affect stem cell fate [4,5] . Furthermore, low oxygen tensions (hypoxia) are necessary to maintain undifferentiated stem cell phenotypes, and also influence proliferation and stem cell fate [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Both extrinsic and intrinsic forces contribute to tissue morphogenesis, homeostasis, and regeneration and affect cell shape, proliferation, and migration (Evans et al 2013). Sensing and transmitting forces depend to a large extent on tight interactions between cell adhesion complexes and the cytoskeleton.…”
mentioning
confidence: 99%
“…p75NTR serves as a low-affnity receptor to mediate diverse functions [9]. Generally, p75NTR is proteolytically cleaved by γ-secretase to generate intracellular domain after ligand activation [10,11]. It is reported that p75NTR interacts with a variety of proteins [12] that in turn induce different pathways [13].…”
Section: Introductionmentioning
confidence: 99%